2015
DOI: 10.1002/ajh.23932
|View full text |Cite
|
Sign up to set email alerts
|

Causes of early death in multiple myeloma patients who are ineligible for high‐dose therapy with hematopoietic stem cell support: A study based on the nationwide Danish Myeloma Database

Abstract: Brentuximab vedotin in combination with extended field radiotherapy as salvage treatment for primary refractory Hodgkin lymphoma To the Editor:Hodgkin lymphoma (HL) is a B-cell derived lymphoid malignancy that accounts for about 10% of all lymphomas. Despite most of patients being cured by modern regimens of chemotherapy and radiotherapy (RT), nearly 20% show primary refractoriness or relapse after initial remission. In these cases second-line chemotherapy followed by autologous stem cell transplantation (ASCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(76 citation statements)
references
References 5 publications
3
71
0
2
Order By: Relevance
“…Until now, only a few studies have focused on EM in MM [15][16][17][18][19][20][21][22][23][24]. Supporting Information Table III highlights the results of these studies, emphasizing the differences in the type of study and the cutoff used to assess EM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, only a few studies have focused on EM in MM [15][16][17][18][19][20][21][22][23][24]. Supporting Information Table III highlights the results of these studies, emphasizing the differences in the type of study and the cutoff used to assess EM.…”
Section: Discussionmentioning
confidence: 99%
“…The Greek Myeloma Study Group showed that renal failure is associated with EM2, ranging from 12% in patients with severe renal failure to 3% in patients with mild or no renal failure. More recently, Holmstr€ om et al [19] presented a nationwide Danish MM database of patients ineligible for high-dose therapy, showing 22% EM6 associated with performance status, ISS, and lactate dehydrogenase. The most common causes of death were infections, cardiovascular failure and renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…A skilled trainee reviewed all cases on-site. The majority of early deaths (50.9%) were caused by infections 14. As a consequence of these findings, DMSG started, in 2013, a randomized, controlled clinical trial to study the efficacy of prophylactic antibiotics within the first 6 months of diagnosis in elderly patients with MM (EudraCT number: 2012-004424-38).…”
Section: Examples Of Researchmentioning
confidence: 99%
“…1 Studies have revealed that infections are the leading cause of early deaths in MM patients. [2][3][4] The majority of infections in MM patients consists of pneumonia and sepsis/septicemia. 1,2,5-8 However, besides results from clinical trials, few studies have addressed the risk factors for serious infections in the era of proteasome inhibitors and IMiDs.Recent single-center studies have analyzed blood stream infections (BSI) in MM; Huang et al 9 showed that the incidence of BSI within 3 months from MM diagnosis was 11.7% and that International Scoring System (ISS) stage III and poor performance status (PS) were independent risk factors for a BSI.…”
mentioning
confidence: 99%